Study on the Prospects of Promoting Dhaka Cloth Production in Nepal - Shrestha, Erene (Tribhuvan University Journal, 2010)
Research Study on the prospects of promoting Dhaka cloth production in Nepal is aimed to explore the present situation and the future prospects of the expansion of Dhaka industry in Nepal. Dhaka cloth is swivel woven through handloom traditional cloth. Its manufacturing is concentrated mainly in Kahtmandu valley, Pokhara and Palpa and in recent years in the hills of eastern Nepal Therathum etc. The research is conducted taking interviews with the owners of Palpali Dhaka Udyog, The rathume Dhaka Udyog Dhaka weaves, Mahaguthi, Dhanakuta sisters entrepreneurs in Kupondole and visiting and interviewing in Gharelu Udyog in Tripureswar and visiting some of the retail shops of Kathmandu valley, where different types of Dhaka are sold from different parts of the countries. A questionnaire is developed to be answered by the retail sellers and another questionnaire was developed by the Dhaka factory owners. The questionnaire include mostly with their production purchases, sales, weaving techniques, yarn used dyeing methods etc. Secondary literature and information are hardly used in this research paper.Possibilities of prospects for the expansion of exports lie in modernization in certain segment of the sectors to ensure the right quality of fabrics used in the garments extension of technical assistance, training and modern techniques and designs. Dhaka weaves export the products in Norvey, Switzerland, Japan, America etc. In the past, it also used to supply in royal family. There is also a good prospect for selling of efficient manufacturing units in the form of export oriented joint ventures in response to the condisreable opportunities available in dynamic export market. Handloom units of the country substituted by the big mills and factories can be organized and modernized for export oriented handloom cloth production if well planned improvement in loom yarn consumption, methods and designs are made.